Homogeneous Groups and the Testing of Economic Hypotheses - Elton, Edwin J.; Gruber, Martin J. (Journal of Financial and Quantitative Analysis, 1970)
In testing hypotheses, researchers are almost always faced with the problem of isolating the effect of certain variables. This is a particularly acute problem in the social sciences, where the absence of an experimental environment means that researchers must resort to statistical methods of adjustment.